2010
DOI: 10.1111/j.1471-0528.2010.02521.x
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus‐based triage of women showing a cervical cytology result of borderline or mild dyskaryosis

Abstract: Please cite this paper as: Arbyn M, Martin-Hirsch P, Wentzensen N. HPV-based triage of women showing a cervical cytology result of borderline or mild dyskaryosis. BJOG 2010;117:641-644.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…Similarly, Castle et al [28 ]demonstrated that cytology combined with HPV 16/18 infection may indicate the immediate risk of CIN3+. The accuracy for detecting CIN2+ by HPV 16/18 and HR-HPV in women with ASC-US and LSIL in our study is consistent with the results of previous studies [12,29]. Genotyping for HPV 16/18 is much more specific, but at the expense of loss in sensitivity in the triage of women with ASC-US and LSIL.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, Castle et al [28 ]demonstrated that cytology combined with HPV 16/18 infection may indicate the immediate risk of CIN3+. The accuracy for detecting CIN2+ by HPV 16/18 and HR-HPV in women with ASC-US and LSIL in our study is consistent with the results of previous studies [12,29]. Genotyping for HPV 16/18 is much more specific, but at the expense of loss in sensitivity in the triage of women with ASC-US and LSIL.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, the study was not subjected to verification bias. Our findings of high sensitivity and high NPV for CIN2+ with hrHPV DNA testing are in accordance with the ASCUS-LSIL Triage Study and a meta-analysis of other HPV-based triage studies; however, these studies have focused on women with borderline or mild cervical dyskaryosis [21][22][23]. In our study, a majority (71%) of the patients had low-grade abnormalities (ASC-US/CIN1) on the initial Pap test after revision ( Table 1).…”
Section: Discussionsupporting
confidence: 75%
“…In women 50 years or older, being hrHPVnegative was linked with a risk of CIN21/AIS1 that could be considered low enough to refer women to a next screening round. [57][58][59] However, in this group of women (AGC on cytology, hrHPV-negative, and 50 years), an elevated risk for extracervical malignancy was observed (risk of nHRC: 18%). The use of HPV DNA triage testing in the initial work-up of AGC, once an important component in the 2006 American guidelines, has been removed in the 2012 guidelines.…”
Section: Discussionmentioning
confidence: 69%
“…). In women 50 years or older, being hrHPV‐negative was linked with a risk of CIN2+/AIS+ that could be considered low enough to refer women to a next screening round . However, in this group of women (AGC on cytology, hrHPV‐negative, and ≥50 years), an elevated risk for extra‐cervical malignancy was observed (risk of nHRC: 18%).…”
Section: Discussionmentioning
confidence: 99%